FlyMsia Airlines / Fatin Nabila Mohd Sahidin ... [et al.] - Mohd Sahidin, Fatin Nabila; Osman, Mohammad Ilyasa Aqeef; Abang Taip, Nurul Syahirah; Abdullah, Nur Sakinah (2021)
This report of the business model canvas is an group project that need all of students in the group to set up new business, which is a real entrepreneurial business. For this project, we have chosen the FlyMsia Airlines as our business because we sure that this company can help people to travel in entire world and help them to get a job. In FlyMsia Airlines, they provide many services to make concerned with customer comfort.